The conceptual design of a stream island index for physical habitat complexity assessment in stream restoration projects - Tallar, Robby Yussac (Frontiers in Built Environment, 2023)
Most literatures on geomorphology, hydraulics or stream ecology contained no mention or less description about stream island, the process, the development or the ecological advantages provided. Due to a lack of information, research and related data, there were no stream island indexes available for indicating the stream island status. Motivated by the fact, the objective of this study is to develop a conceptual design of Stream Island Index (SII) as a template for physical habitat complexity assessment in stream restoration projects. Specific purposes included: (a) to examine the stream island conceptual models; (b) to develop obvious and comprehensive explanations of the stream island development by considering attributes from the geomorphology, hydraulics and ecological perspective. This study used AHP method as follows screening and selecting attributes, transforming and developing sub-indices, assignment of weights, and formulating an index. The conclusion is a Stream Island Index (SII) combines the measures of selected physical habitat quality indicators to produce a single dimensionless number, and a novel approach to communicate information on stream island quality status to the public and related policy makers. It seems essential that a serious attempt be developed to design a system that can identify the overall stream island condition. Once a generalized stream island system is set up as a controlling framework, supplementary indexes for specific purposes and location can be added. Therefore, the SII is a promising new tool for stream restoration practitioners, and it has the potential to make a significant contribution to improving the success of stream restoration projects.